The Emergency in English Speaking Proficiency Among Non-Native Learners - Dzikrillah, Cinta Ala; Faruk, Ahmad (Institut Agama Islam Negeri Palopo, 2025)
This study aims to identify and analyze the main factors that cause limitations in English speaking skills in non-native learners, focusing on speaking anxiety, learning environment, and teaching methods. The focus of the study is directed at the interaction between psychological, environmental, and pedagogical factors in influencing the development of speaking skills. The research method used is qualitative with a descriptive approach, involving in-depth interviews, classroom observations, and analysis of the results documentation. Data were analyzed to identify patterns and relationships between these factors. The results showed that speaking anxiety is a major barrier that is exacerbated by lack of exposure to English, monotonous grammar- based teaching, and minimal opportunities for speaking practice. Observations revealed avoidance of speaking and the dominance of the use of the mother tongue in the village, documentation analysis showed low scores youth on aspects of fluency and pronunciation. This study contributes to the development of new perspectives in English language learning by emphasizing the importance of integrating practice-based approaches, technology, and supportive learning environments. The results provide practical insights for educators in designing more effective learning strategies to improve the speaking skills of non-native students.